Alpine Skiing With total knee ArthroPlasty (ASWAP): metabolism, inflammation, and skeletal muscle fiber characteristics. (August 2015) - Kristensen, M.; Pötzelsberger, B.; Scheiber, P.; Bergdahl, A.; Hansen, C. N.; Andersen, J. L.; Narici, M.; Salvioli, S.; Conte, M.; Müller, E.; Dela, F.
Abstract : We investigated the effect of alpine skiing for 12 weeks on skeletal muscle characteristics and biomarkers of glucose homeostasis and cardiovascular risk factors. Twenty‐three patients with a total knee arthroplasty (TKA) were studied 2.9 ± 0.9 years (mean ± SD) after the operation. Fourteen patients participated in the intervention group (IG) and nine in the control group (CG). Blood samples and muscle biopsies were obtained before (PRE) and 7.3 ± 0.8 days after (POST) the intervention, and blood samples again after a retention (RET) phase of 8 weeks. With skiing, glucose homeostasis improved in IG (decrease in fasting insulin, increase in muscle glycogen) but not in CG. Fiber type distribution and size, as well as capillary density and number of capillaries around the fibers (CAF), were not different between the operated and the non‐operated leg in either group. The relative number of type I fibers increased with skiing in IG with no change in CG. Inflammatory biomarkers, plasma lipids, and mitochondrial proteins and activity did not change. Alpine skiing is metabolically beneficial and can be used as a training modality by elderly people with TKA.